493. Clinical and Epidemiological Features of Healthcare Workers Detected with Coronavirus Disease. (31st December 2020) - Campbell, Melissa; Datta, Rupak; Wyllie, Anne; Casanovas-Massana, Arnau; Handoko, Ryan; Sewanan, Lorenzo; Ko, Albert I; Martinello, Richard A
Abstract: Background: Data early in the SARS-CoV-2 pandemic suggested frontline healthcare workers (HCW) may account for 10–20% of all infections. CDC estimated 600, 000 infections in HCWs. Symptom screening is a strategy to prevent healthcare-associated transmission. This method may not identify asymptomatic or pre-symptomatic carriers. Methods: We conducted a prospective cohort study in asymptomatic or minimally symptomatic healthcare workers in a 1541-bed academic medical center. Although recruitment began in designated COVID-19 units, we expanded to all HCWs providing care to hospitalized patients during the pandemic. Data was gathered on demographics, work area in the hospital and daily questionnaires were sent listing symptoms of SARS-CoV-2. Protocol included twice weekly self-collected nasopharyngeal swab and saliva for SARS-CoV-2 N1 and N2.Those with positive PCR result, underwent telephone survey to assess symptomatology and severity of illness. Results: A total 525 HCWs began the study protocol and 16 were identified as PCR positive. Samples included concordant saliva and NP samples on 9 (56%), exclusively NP samples on 5 (31%) and 2 (12%) HCWs were positive by saliva PCR only. Majority were female, and all were nursing staff; with 19% reported not working in a designated COVID-19 unit. During the course of this active surveillance, universal masking was mandated in the institution. Rhinorrhea and headache were reported by 6 (38%), 5 (31%) reported cough and 3 (19%) developed myalgia. Changes in smell and taste preceded the positive PCR test in 2 (12%). One HCW reported developing a fever with acute illness. All were notified about their PCR positive status by institution's occupational health department and self-isolated to monitor for symptoms. Conclusion: The spectrum of disease in this HCW cohort is similar to mild disease in the community. Due to high incidence of asymptomatic or mildly symptomatic HCWs, active surveillance with routine testing proves be beneficial to prevent hospital transmission of SARS-CoV-2. Universal masking significantly decreased the HCW positive rate in our study, underscoring the need for universal efforts to mitigate healthcare-associated transmission with self-monitoring, face mask use, and other infection prevention behaviors like hand hygiene. Disclosures: All Authors : No reported disclosures